South Asia's security : primacy of internal dimension - Iftekharuzzaman (Vikas Publishing house, 1995)
Papers presented at the International Seminar on South Asia's Security in the 1990s: Primacy of Internal Dimension, on 5-7 January 1992, organized by the Bangladesh Institute of International and Strategic Studies at Dhaka, Bangladesh.